Two novel species and two new records of Distoseptispora from freshwater habitats in China and Thailand - Hong-Wei Shen (Pensoft Publishers, 2021)
During investigations into freshwater fungi from the Great Mekong Subregion, four Distoseptispora taxa were collected from China and Thailand. Based on morphological characteristics, and phylogenetic analyses of combined LSU, ITS, SSU, TEF1-α, and RPB2 sequence data, two new species Distoseptispora bangkokensis and D. lancangjiangensis are introduced, and two known species D. clematidis and D. thysanolaenae were first reported in freshwater habitat. Illustrations and descriptions of these taxa are provided, along with comparisons with extant taxa in the genus.